TO DETERMINE THE FREQUENCY OF ALDEHYDE DEHYDROGENASE TYPE 2 (ALDH2) DEFICIENCY IN APLASTIC ANAEMIA: A SINGLE CENTER EXPERIENCE FROM PAKISTAN - Shamim, Noor; Mehreen Ali Khan,; Raheel Iftikhar,; Zaineb Akram,; Hina Jamshaid,; Jahanzeb Rehman,; Qamar un Nisa Chaudhry,; Tariq Ghafoor, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Aplastic anaemia is a rare bone marrow failure syndrome and is defined by pancytopenia associated with a hypo-cellular bone marrow with no increase in reticulin and in the absence of any abnormal infiltrate. The objective of the study was to determine the frequency of Aldehyde Dehydrogenase type 2 (ALDH2) deficiency in patients with Aplastic Anaemia and investigate its correlation with patient and disease characteristics. It was a descriptive cross-sectional study conducted at Armed Forces Bone Marrow Transplant Centre Rawalpindi from 01-08-2022-01-02-2023, over a period of 6 months. Methods: A total of 56 patients who were diagnosed with aplastic anaemia during this period, fulfilling inclusion criteria were enrolled. Patients were genotyped as GG (homozygous) and GA (heterozygous). GG had normal ALDH2, while GA were patients with ALDH2 deficiency. Data was collected on the patient's demographics, type and severity of anaemia, type of hematopoietic stem cell transplant (HSCT) and frequency of ALDH2 deficiency. Results were analyzed for ALDH2 deficiency and its correlation with patient and disease characteristics was investigated. Results: A total of 56 patients were included in the study. The median age of the patients was 28 years (20-39). According to the type of aplastic anaemia, 2 (3.6%) had Fanconi anaemia and 54 (96.4%) had acquired aplastic anaemia. In our study, 18 (32.1%) patients had undergone HSCT while the remaining 38 (67.9%) could not undergo HSCT. The frequency of the presence of ALDH2 deficiency was 2 (3.6%). There was no statistically significant correlation between the frequency of ALDH2 deficiency with variables like gender, age distribution, type of aplastic anaemia, the severity of aplastic anaemia and hematopoietic stem cell transplant. Conclusion: We concluded from our study the frequency of ALDH2 was rare in patients with aplastic anaemia. There was no statistically significant co-relation between the frequency of ALDH2 deficiency with variables like gender, age distribution, type of aplastic anaemia, the severity of aplastic anaemia and hematopoietic stem cell transplant.